KARAKTERISASI RESERVOIR MENGGUNAKAN METODE INVERSI LAMBDA MU RHO (LMR) DAN ELASTIC IMPEDANCE PADA LAPANGAN ‘X’ - Dian L Silalahi; Udi Harmoko; M. Razi (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2013)
Lambda Mu Rho (LMR) inversion method has been used to diagnose the validity of the brightspot concept as the indication of the existance of hidrocarbon fluid and to find the sandstone lithology distribution of ‘X’ field with validation lithology by using the result of Elastic Impedance (EI) inversion. In fact the existance of brigthspot apparently not always be the indication of the hidrocarbon fluid and sand stone. The application of Lambda Mu Rho inversion method was able to indicates the existance of the hidrocarbon fluid and lithology well by using the incompressibility and rigidity of the rocks. The target zone was Z2260 layer with lithologies of sandstone and shale.Inversion analysis showed the distribution of fluid hidrocarbon and sandstone through indication of the low value of the incompressibility and high value of the rigidity in the target zone. The value of incompressibility dan rigidity is obtained from the data log crossplot which is then used as a reference to determine the distribution of the hidrocarbon and lithology through map inversion. To give a certain type of lithologies we made validation using the result of EI inversion which is sensitive to distinguish the lithologies.LMR inversion result showed hidrocarbon fluid distribution in layer Z2260 with Lambda Rho value 33 to 44 Mpa*gr/cc, the distribution of sandstone lithology with Mu Rho value 30 to 35 Mpa*gr/cc. The lithology was validated by the result of EI inversion which able to show the distribution of sandstone lithology in the Z2260 layer with value 8000 to 9800 (m/s)2*gr/cc. Keywords: Inversion, Lambda Mu Rho (LMR), Elastic Impedance (EI), sandstone, hidrocarbon.